Understanding farmers’ eco-friendly fertilization technology adoption behavior using an integrated S-O-R model: The case of soil testing and formulated fertilization technology in shaanxi, china - Dong, Hao; Wang, Bo; Han, Jichang; Luo, Lintao; Wang, Huanyuan; Sun, Zenghui; Zhang, Lei; Dai, Miao; Cheng, Xiaohui; Zhao, Yunliang (Frontiers in Environmental Science, 2022)
To explore the formation mechanism of farmers' willingness to adopt eco-friendly fertilization technology (EFFT), which is important to promote the application of farmland conservation technologies and enhance the effect of farmland quality protection. Based on the extended stimulus-organism-response (S-O-R) theoretical analysis framework, this paper selects 295 field interview data of farmers in the high standard farmland grain main production area in Shaanxi Province, and uses the Partial least square structural equation model (PLS-SEM) of formative indicators to analyze the mechanism of external incentives on farmers' eco-friendly fertilization technology adoption behavior and the mediating effect of intrinsic perception and moderating effect of the family endowment. The results show that external incentives can effectively improve farmers' technology adoptive behavior; internal perception has a significant positive effect on adoptive behavior, and it plays an intermediary role between external incentives and eco-friendly fertilization technology adoption behavior; family endowment has a significant positive effect on farmers' technology adoption behavior, but the moderating effect of family endowment in external incentive-technology adoption behavior relationship is not significant. Therefore, we should choose appropriate and flexible government regulations, and give full play to the role of premium incentives, so as to improve the motivation of farmers to adopt eco-friendly fertilization technology.